‘Quality in the eye of the beholder: developing an empirical scale for video-on-demand services’ - Satyaki Datta; Tathagata Ghosh (Cogent Social Sciences)
This research addresses a critical gap in the literature by developing a comprehensive, empirically validated scale for assessing Video-on-Demand (V-o-D) service quality within digital entertainment. Through a robust mixed-method approach involving around 900 participants across several studies, the research identifies and empirically validates a 30-item scale structured into seven distinct dimensions – Ease of use, Content mix, Genre variety, Subscription easiness, Regulation free, Search & recommend and New release. Grounded in the Means-End Chain (MEC) theory and tested against the Theory of Consumption values (TCV), the study establishes the multidimensional nature of V-o-D service quality and its significant positive impact on the five consumption values. This research pioneers the systematic measurement of V-o-D service quality. Practically, the findings equip V-o-D marketers with strategic insights into consumer expectations, facilitating targeted differentiation and enhanced consumer engagement strategies in an increasingly competitive digital marketplace. Future research avenues are identified, emphasizing cross-cultural validations and extensions into other digital entertainment services, reinforcing the scale’s global applicability and academic rigour.